Justice and Fairness in the City : A Multi-Disciplinary Approach to 'Ordinary' Cities - Bell, Derek, 1968-; Davoudi, Simin (Book collections on Project MUSE., 2017)
This work examines the theory and practice of justice in and of the city through a multi-disciplinary collaboration, which draws on a wide range of expertise. It will be a valuable resource for academic researchers and students across a range of disciplines including urban and environmental studies, geography, planning, education, ethics and politics.